2012
DOI: 10.1210/jc.2012-2389
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Three Different Cumulative Doses of Intravenous Methylprednisolone for Moderate to Severe and Active Graves' Orbitopathy

Abstract: The 7.47-g dose provides short-term advantages over lower doses. However, this benefit is transient and associated with slightly greater toxicity. The use of a cumulative dose of 7.47 g of methylprednisolone provides short-term advantage over lower doses. This may suggest that an intermediate-dose regimen be used in most cases and the high-dose regimen be reserved to most severe cases of GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
289
6
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(344 citation statements)
references
References 30 publications
13
289
6
20
Order By: Relevance
“…To the best of our knowledge, there were 2 randomized clinical trials investigating the optimal dose and schedule of iv GC therapy [16,17]. When Bartalena et al compared the safety and efficacy of 3 low-dose iv GC regimens (cumulative doses of 2.25 g, 4.98 g, and 7.47 g), they concluded that the higher-dose regimen provided a short-term advantage in efficacy, but had slightly greater toxicity [16]. In this study, although the HD group had slightly better changes in ophthalmic parameters and response rates, no statistically significant differences were detected in ophthalmic parameters or the safety profile between patients on the 2 regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there were 2 randomized clinical trials investigating the optimal dose and schedule of iv GC therapy [16,17]. When Bartalena et al compared the safety and efficacy of 3 low-dose iv GC regimens (cumulative doses of 2.25 g, 4.98 g, and 7.47 g), they concluded that the higher-dose regimen provided a short-term advantage in efficacy, but had slightly greater toxicity [16]. In this study, although the HD group had slightly better changes in ophthalmic parameters and response rates, no statistically significant differences were detected in ophthalmic parameters or the safety profile between patients on the 2 regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Since this is not a standard method for comparing SIRs from different MRI scanners, this approach requires further verification. We did not define the outcome of GO by evaluating a combination of changes in ophthalmic parameters because we were not able to collect complete information about ophthalmic parameters that were evaluated in prior large prospective studies [16,17]. For example, we were not able to obtain grades in each class of the NOSPECS classification from the patients' medical records.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment effectiveness much depends on interindividual variability, but this does not seem to be related to polymorphisms of the GC receptor (56). Intravenous pulsed methylprednisolone is more effective (14,46,57,61) and has a better safety profile compared with oral prednisone (60,61,62,63,64,65). Different treatment schedules have been used, with cumulative doses ranging from 4.5 to 12 g and occasionally associated with oral GC interpulse or at the end of the protocol (3,14,54,55,56,57,58,59).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Different treatment schedules have been used, with cumulative doses ranging from 4.5 to 12 g and occasionally associated with oral GC interpulse or at the end of the protocol (3,14,54,55,56,57,58,59). A recent multicenter randomized EUGOGO study has shown that a cumulative dose of 7.5 g of methylprednisolone is more effective than intermediate or lower doses (5 or 2.25 g respectively), although it is associated with more frequent adverse events (65). In particular, the high-dose regimen has a more significant and positive impact on eye muscle motility compared with lower doses.…”
Section: Glucocorticoidsmentioning
confidence: 99%
See 1 more Smart Citation